Pengaruh pengungkapan economic, environmental, social, dan governance terhadap kinerja keuangan pada perusahaan sektor non keuangan yang terdaftar di bursa efek Indonesia periode 2017-2022 - Puspaaji, Defy Maulida; Hartono, Ulil (Jurnal Ilmu Manajemen, 2024)
Increasing environmental problems have made the concept of sustainability in Indonesia more popular. The sustainability concept has successfully invited companies to carry out sustainability reporting every year. This research analyses the influence of economic, environmental, social and governance disclosures on company financial performance. This research chooses ROA as the dependent variable and economic, environmental, social, and governance aspects as independent variables. The population used is companies in the non-financial sector listed on the Indonesia Stock Exchange for 2017 - 2022. Using the purposive sampling method resulted in 30 companies as research samples with the condition that the companies publish annual and sustainability reports. Data analysis in this test utilises panel data regression analysis using STATA 15 software. The test results state that economic, environmental, and social aspects do not affect financial performance. In contrast, governance aspects have a significant negative effect on financial performance with implications that can be done when you want to know the financial performance of a company, investors must consider the governance aspect.